Penerapan Asuransi Syariah Unit Link di Indonesia - Santi, Mei (LIPI, 2018)
In its application, unit link sharia insurance practices in Indonesia have referred to the DSN MUI fatwa and are accompanied by a sharia supervisory board (DPS) that has been appointed for each company, as well as under the supervision of the financial services authority (OJK) so that it is expected in accordance with applicable provisions in Indonesia. And can encourage the growth of unit link Islamic insurance services that are getting stronger and become a milestone in Indonesia.